The role of neutrophil extracellular traps in cancer progression and thrombosis development - J. Kh. Khizroeva; Z. D. Aslanova; A. G. Solopova; V. O. Bitsadze; А. V. Vorobev; А. Yu. Tatarintseva; J.-С. Gris; I. Elalamy; N. А. Makatsariya; D. V. Blinov (Акушерство, гинекология и репродукция, 2024)
Introduction. Initially discovered as a mechanism to protect host neutrophils from pathogens and prevent spread of infection outside inflammatory site, neutrophil extracellular traps (NETs) have been implicated in progression of other diseases associated with sterile inflammation such as autoimmune diseases, diabetes, and cancer. NETs components (myeloperoxidase, citrullinated histones, cell-free DNA) exhibit manifold effects on tumor cells, thereby emphasizing a need to be aware of the features of biological functions related to their constituents and their place in carcinogenesis to identify major molecular targets for targeted therapy of gynecologic cancers in the future.Aim: to determine an impact of NETs on tumor progression/metastasis and thrombosis risk in gynecologic cancer.Materials and Methods. A single-center interventional study was conducted: 70 women with uterine, ovarian and cervical cancer were examined; 60 age-matched apparently healthy women without thrombotic complications were selected as controls. All study participants were examined for myeloperoxidase (MРO), citrullinated histone (сitH3), proinflammatory cytokine interleukin-1β (IL-1β), and neutrophil/lymphocyte ratio (NLR).Results. Laboratory biomarkers such as MPO (p < 0.001), IL-1β (p < 0.001) and NLR (p = 0.003) were significantly more often elevated in patients with oncological pathology compared to group of healthy women. 32 (45.7 %) of the 70 women with cancer of the reproductive system had metastases. Metastases-related analysis in patients showed significant differences in MPO level (p = 0.002), but not in level of citH3, IL-1β and NLR (p = 0.441, p = 0.159, and p = 0.739, respectively). Elevated citH3 vs. MPO, IL-1β and NLR level was significantly more often associated with developing thrombosis in study patients (p < 0.001).Conclusion. The results of our study demonstrate that inflammation and NETs components such as MPO and citH3 may be potentially implicated in many aspects of carcinogenesis including tumor metastasis and the risk of developing thrombosis in cancer patients.